2003
DOI: 10.1046/j.1440-172x.2003.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing management of fever in children: A systematic review

Abstract: The primary purpose for intervening when a child has a fever is to increase the child's comfort. This consideration should be weighed against any harm that might result from intervening. There was a lack of evidence to support the routine use of sponging. The administration of paracetamol should be used selectively and with caution. In summary, care needs to be individualised, based on current knowledge of the effectiveness and risks of interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0
17

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 16 publications
0
41
0
17
Order By: Relevance
“…All five studies found the combination more effective than sponging alone (Watts et al 2001) Four (Freidman & Barton, 1990;Kinmonth et al, t992;Steele et al , 1970;Teo et al, 1998) of the five research teams reported a statistical significance (p = 0.003); while one (Hunter, 1973) did not include a statistical analysis. All five studies found the combination more effective than sponging alone (Watts et al, 2001). Three did not report a significant difference and one (Kinmonth, 1992) did not report on the statistical significance (Watts et al, 2001).…”
Section: Acetaminophen and Sponging Compared To Spongingmentioning
confidence: 97%
See 4 more Smart Citations
“…All five studies found the combination more effective than sponging alone (Watts et al 2001) Four (Freidman & Barton, 1990;Kinmonth et al, t992;Steele et al , 1970;Teo et al, 1998) of the five research teams reported a statistical significance (p = 0.003); while one (Hunter, 1973) did not include a statistical analysis. All five studies found the combination more effective than sponging alone (Watts et al, 2001). Three did not report a significant difference and one (Kinmonth, 1992) did not report on the statistical significance (Watts et al, 2001).…”
Section: Acetaminophen and Sponging Compared To Spongingmentioning
confidence: 97%
“…All five studies found the combination more effective than sponging alone (Watts et al, 2001). Three did not report a significant difference and one (Kinmonth, 1992) did not report on the statistical significance (Watts et al, 2001). In this systematic review (Watts et al, 2001) examining a total sample of 821 children, one febrile seizure (0.12%) was reported (Agbolosu et al, 1997;Watts et al, 2001) during the study.…”
Section: Acetaminophen and Sponging Compared To Spongingmentioning
confidence: 98%
See 3 more Smart Citations